Penerapan Firebase Realtime Database Pada Prototype Aplikasi Pemesanan Makanan Berbasis Android - George Richard Payara; Radius Tanone (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
In this modern era, the action of information retrieval process and meals ordering in the culinary business become a trending issue, from the information about the lowest until the expensive prices, and from the foods stalls until the luxurious restaurant. One of the samples in Warung Lawas in Salatiga city, whereas the process of searching and ordering foods are still manual which is the customers must find the place to eat and order the meals manually, therefore the process of culinary business in this present time is not really effective yet in saving the time. Nowadays, by employing firebase technology named ‘realtime database’ which is highly developed, for this reason an application to order the meals is made by using ‘cloud computing’ technology with ‘realtime database’ firebase based on Android. The use of ‘realtime database’ firebase aims to transfer the data ‘realtime’ because in that way the process of ordering by using the application will be faster. The result of this research is to point out that the system that had been made to help the user in ordering the meals in Warung Lawas Salatiga turns into being more effective and efficient.